REFORMULATION OF NOTARY PROTOCOL ARCHIVE STORAGE ARRANGEMENTS IN DIGITAL FORM - Risqi Kurniawan; Rahmatul Hidayati (SOSIOEDUKASI, 2026)
The rapid advancement of information and communication technology has significantly transformed various aspects of human activity, including the notarial profession. As a public official authorized to create authentic deeds, a notary is also responsible for maintaining the notarial protocol as legal evidence of every deed executed. However, the current archival system for notarial protocols in Indonesia remains largely manual and paper-based, leading to several challenges such as limited storage capacity, vulnerability to physical deterioration, and inefficiency in reporting and supervision processes. These conditions demonstrate the urgent need for reformulating the regulatory framework governing the storage of notarial protocols to align with digital transformation and the demands of modern legal administration. This study aims to comprehensively analyze the existing regulations on notarial protocol storage, evaluate the opportunities and challenges of digital archiving, and propose an appropriate reformulation aligned with Indonesia’s positive legal principles. The research employs a normative legal method using statutory and conceptual approaches. Primary legal materials include the Law on Notary Office (UUJN), the Electronic Information and Transactions Law (UU ITE). Secondary materials consist of literature, academic journals, and related research that support theoretical and practical analysis. The findings reveal that the current regulatory framework under the UUJN remains conventional and does not explicitly accommodate digital storage mechanisms. The digitalization of notarial protocols offers several advantages, such as efficient use of storage space, enhanced accessibility, faster reporting, and transparent supervision by the Notary Supervisory Council. Nevertheless, it also presents challenges, including data breach risks, authenticity verification issues, and unequal digital infrastructure across regions. To address these issues, this study recommends an integrative reformulation of the UUJN, UU ITE. Such reformulation should establish clear technical standards for digital storage, electronic supervision mechanisms, and strong data security through certified electronic signatures and national encryption systems. The implementation of these measures is expected to foster a modern, secure, and accountable notarial archival system that guarantees legal certainty and protection for society in the digital era.